(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 1998)
Truffaut’s concern in “La nuit américaine” (“Day for Night”): that the main actor would die before finishing the film. The reporter’s concern: was that the recorder wouldn’t work during an interview. Like now. New batteries, blank cassette, prepared questionnaire, the customary test: “interview with me, five, four, three, two, one,” and yet… The cassette gets stuck, the tape devoured between accordion and sweetmeat (Document excerpt).